Immersion treatment for exertional hyperthermia: Cold or temperate water? - Casa, D. J.; Kenny, G. P.; Taylor, N. A. S. (Medicine & Science in Sports & Exercise, 2010)
Our viewpoint in this Contrasting Perspective stems from the primary consideration that: Cold water cools faster than other cooling modalities. This minimizes the amount of time an exertional heat stroke (EHS) victim is severely hyperthermic, which dictates outcome. Current evidence strongly indicates that rapid cooling via cold/ice water optimizes survival of persons with EHS. This article reviews - Physiological and biophysical considerations, - Medical considerations - cooling efficiency and survival rates, - Esophageal versus rectal temperature, - Cutaneous circulation, - Heat loss, - Body mass and - Adverse effects from contrasting perspectives.